Physiologically based pharmacokinetic modeling to predict the pharmacokinetics of codeine in different CYP2D6 phenotypes - Yang, Yujie; Zhang, Xiqian; Wang, Yirong; Xi, Heng; Xu, Min; Zheng, Liang (Frontiers in Pharmacology, 2024)
Objectives Codeine, a prodrug used as an opioid agonist, is metabolized to the active product morphine byCYP2D6. This study aimed to establish physiologically based pharmacokinetic (PBPK) models of codeine and morphine and to explore the influence of CYP2D6 genetic polymorphisms on the pharmacokinetics of codeine and morphine.Methods An initial PBPK modeling of codeine in healthy adults was established using PK-Sim ® software and subsequently extrapolated to CYP2D6 phenotype-related PBPK modeling based on the turnover frequency (Kcat) of CYP2D6 for different phenotype populations (UM, EM, IM, PM). The mean fold error (MFE) and geometric mean fold error (GMFE) methods were used to compare the differences between the predicted and observed values of the pharmacokinetic parameters to evaluate the accuracy of PBPK modeling. The validated models were then used to support dose safety for different CYP2D6 phenotypes.The developed and validated CYP2D6 phenotype-related PBPK model successfully predicted codeine and morphine disposition in different CYP2D6 phenotypes. Compared with EMs, the predicted AUC0-∞of morphine was 98.6% lower in PMs, 60.84% lower in IMs, and 73.43% higher in UMs. Morphine plasma exposure in IMs administered 80 mg codeine was roughly comparable to that in EMs administered 30 mg codeine. CYP2D6 UMs may start dose titration to achieve an optimal individual regimen and avoid a single dose of over 20 mg. Codeine should not be used in PMs for pain relief considering its insufficient efficacy.The PBPK modeling can be applied to explore the dosing safety of codeine and can be helpful in predicting the effect of CYP2D6 genetic polymorphisms on drug-drug interactions of codeine in the future.